Validity of session rating of perceived exertion for measuring training load in youth team handball players - Pedersen, A.; Randers, M. B.; Luteberget, L. S.; Moller, M. (The Journal of Strength and Conditioning Research, 2023)
Session rating of perceived exertion (sRPE) is a subjective self-reported measure of training load and is a popular method in several different team sports. This study aimed to investigate the validity of sRPE, by correlating sRPE load (sRPE × minutes of training) and heart rate (HR) expressed as Edwards Summated Heart Rate Zones (SHRZ) and PlayerLoad among Danish youth team handball players. Second, the study aimed to investigate sRPE load's ability to descriptively differentiate between a low and a high training load category. A comparative cross-sectional study was conducted in the in-season period. Fourteen training sessions were measured from 6 teams, in which PlayerLoad, Edwards SHRZ, and sRPE load were measured for the training session and collected from 47 subjects (23 males and 24 females). Pearson's product-moment correlation coefficients were calculated between sRPE load and Edwards SHRZ and PlayerLoad. Furthermore, a high and a low load category were made from PlayerLoad or Edwards SHRZ to investigate sRPE load's ability to discriminate between high and low objective load. Large correlations between sRPE load and Edwards SHRZ (0.52 [95% CI 0.27:0.70]) and between sRPE load and PlayerLoad (0.67 [95% CI 0.47:0.80]) were observed. Our findings further indicate that sRPE load can differentiate between a high and a low training load category in both Edwards SHRZ and PlayerLoad. Our results show that sRPE load reflects both internal and external load during team handball training sessions and seems to discriminate between high- and low-intensity training sessions. These results support the validity of sRPE load for measuring training load in young team handball players.